2020
DOI: 10.1021/acsami.0c10924
|View full text |Cite
|
Sign up to set email alerts
|

Screen-Printed High-Performance Flexible Electrothermal Films Based on Three-Dimensional Intercalation Graphene Nanosheets/MWCNT/Carbon Black Composite

Abstract: A liquid-phase stripping method was used to strip the graphite under the action of mechanical shear force to prepare graphene nanosheets (GNSs) on a large scale. Given the multicomponent composite conductive particles formed by GNSs with acid-treated MWCNTs (f-MWCNTs) and carbon black (CB), the three-dimensional (3D) intercalation electrothermal composite of GNSs/MWCNTs/CB with excellent conductivity and mechanical properties was prepared with water-based acrylic resin as a connector. Carbon particles (16.97 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…From Figure 1, we can see that the folded and ultrathin GNSs are produced by liquid-phase stripping of Gt, which we have demonstrated in detail in previous work. 20,21 Figure 1b shows the morphology of carbon particles prepared by ball milling in the control experimental group. It can be seen that the particle size of CB after ball milling is mostly around 25 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From Figure 1, we can see that the folded and ultrathin GNSs are produced by liquid-phase stripping of Gt, which we have demonstrated in detail in previous work. 20,21 Figure 1b shows the morphology of carbon particles prepared by ball milling in the control experimental group. It can be seen that the particle size of CB after ball milling is mostly around 25 nm.…”
Section: Methodsmentioning
confidence: 99%
“…This work is based on the unique natural suspension stability of biological polysaccharide xanthan gum, combined with the excellent conductivity of carbon nanoconductive nanocomposites, long-term stability in the air environment, no harmful gas emissions, and other advantages, to prepare writable water-based environmental friendly graphene nanosheets (GNSs)/multiwalled carbon nanotubes (MWCNTs)/carbon black (CB) nanocomposite conductive ink. On the basis of our previous work, , the mass fraction of resin and conductive carbon materials in ink is reduced, and the stability and rheological properties of the ink are improved. GNSs were prepared by a liquid-phase stripping method, and formed a composite conductive filler with acid-treated MWCNTs (f-MWCNTs) and carbon black (CB).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that the thermoelectric performance of TEG increased by using assisting materials, i.e., the conducting polymer and highly electrically conductive carbon black CB, and by introducing Bi 2 Te 3 with CNTs, and vice versa [22,62,68,75,87]. Young Du et al studied the effect of carbon black on the thermoelectric performance of a Bi 2 Te 3 -based thermoelectric generator.…”
Section: Organic-inorganic and Hybrid Matrixmentioning
confidence: 99%
“…Conductive carbon black (CB) is a kind of amorphous carbon with a large specific surface area, and the particle size is usually about 20–40 nm. Our previous research found that it can efficiently fill the network between GNSs and CNTs, so as to effectively reduce the percolation threshold …”
Section: Introductionmentioning
confidence: 99%